Antiangiogenic activity of 5-bromoindole carbothioamide derivative in ex vivo, in vivo, and in vitro experimental study - Zainab M. Ali; Haitham Mahmood Kadhim; Omeed M. Hassan; Ammar Kubba; Zeena A. Hussein; Hayder B. Sahib (Pensoft Publishers, 2024)
The study aimed to investigate the antiangiogenic, antioxidant, and cytotoxicity activity of a carbothioamide indole derivative. The 2-NPHC activity was evaluated using the ex vivo rat aorta ring assay, the in vivo chick chorioallantois membrane assay, the DPPH assay for scavenging activity, and the expression of the VEGF gene in colon cancer cell line (HCT116). The 2-NPHC had significant antiangiogenic activity in a dose-dependent manner in the rat aorta assay. 2-NPHC managed to reduce the DPPH free radical in a concentration-dependent, 2-NPHC had low to non-toxic effects on the HUVEC cell line, with an IC50 value of 711.7 μg/ml. The VEGF gene expression in the HCT116 cell line reduced the target gene expression compared to control cells. In conclusion, 2-NPHC exhibited significant inhibition of the angiogenesis process, either directly by inhibiting the release or activity of VEGF or indirectly through its antioxidant properties.